Strong second-harmonic generation in silicon nitride films - Ning, Tingyin; Pietarinen, Henna; Hyvärinen, Outi; Simonen, Janne; Genty, Goëry; Kauranen, Martti (Applied physics letters, 2012)
We observe strong second-harmonic generation from silicon nitride films prepared on fused silica substrates by plasma enhanced chemical vapor deposition. The components of the second-order nonlinear optical susceptibility tensor of the films are calibrated against quartz crystal. The dominant component has the magnitude of 2.5pm/V, almost two orders of magnitude larger than reported for Si 3 N 4 , and about three times larger than for the traditional nonlinear crystal of potassium dihydrogen phosphate. The results indicate that silicon nitride has great potential for second-order nonlinear optical devices, especially in on-chip nanophotonics.